Erenumab for episodic migraine prophylaxis. (3rd August 2019) - Overeem, Lucas Hendrik; Neeb, Lars; Reuter, Uwe
ABSTRACT: Introduction : This paper reviews placebo-controlled randomized double-blind studies with erenumab for the prevention of migraine. Erenumab is a fully human monoclonal antibody (mAb), which specifically blocks the calcitonin gene-related peptide (GGRP) receptor. Areas covered : This manuscript was based on articles written in English located on PubMed using the following search terms: episodic and chronic migraine, migraine prophylaxis and prevention, CGRP, CGRP receptor, CGRP receptor antagonist, erenumab, treatment failures, and trigeminal nerve. Expert commentary : The primary endpoints in Phase II and III preventive episodic migraine trials have been reached successfully, and so have multiple secondary endpoints. Monthly subcutaneous injections of either erenumab 70 mg or 140 mg reduced mean monthly migraine days (MMDs) after 3 and 6 months significantly greater than placebo when compared to baseline values with an onset of action within the first week. About 50% of subjects have at least a 50% reduction of MMDs. Several patient-reported outcome measures demonstrate improved quality of life with erenumab. This antibody also shows efficacy in a prior preventive treatment failure population. The tolerability of erenumab is good, which is reflected by low dropout rates in all erenumab clinical trials. Within the first year of treatment, no specific group or type of adverse events were observed.